Cognitive Enhancement of Sports Persons Using Multiple Object Tracking - Rawat, Jayesh (My University, 2014)
The study inspected and investigated the electroencephalographic signals of a sports person during the Multiple Object Tracking (MOT) task and their responses to various tests of cognitive assessment battery (cogstate) and D2 test after being provided with appropriate enhancement training. Nineteen healthy sports persons contributed in this study, of which 12 were trained with proper intervention and seven were counted in the control group. Cognitive enhancement, i.e., advancement or betterment of mental abilities, is initiated with assessing cognitive abilities. In the present research work, intervention was delivered through MOT. The physiological signals (EEG) were acquired during MOT, cogstate assessments and D2 test as a part of pre-recording followed by intervention through MOT itself and there after post recording was carried out with same tests. MATLAB (EEGLAB TOOLBOX, WAVELET) and comparison of the various features was done for analysis. The accuracy was calculated using Support Vector Machine (SVM) and Linear Discriminant Analysis (LDA) classifiers. Results after comparing pre and post intervention physiological signals showed beta/theta ratio of power in FC5 and FC6 increases in case of selective attention and power of alpha band increases in channels F3, F4, O1 and O2. For selective attention, the accuracy using SVM found 66.67% and with LDA was 68.42%, whereas working memory was found 55.56% and 57.89% respectively. The pre-intervention and post-intervention results were also compared using t-test for the purpose of significance.
ME, EIED
Keywords: Cognitive Enhancement; Sports Persons; Multiple Object Tracking